The effects of situational leadership and self-efficacy on the improvement of teachers’ work productivity using correlation analysis and SITOREM - Hidayat, Rais; Patras, Yuyun Elizabeth; Hardhienata, Soewarto; Agustin, Rindu Rahayu (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
This research aimed to determine the positive correlation of situational leadership and self-efficacy with the improvement of teacher work productivity. The quantitative method with correlation analysis were employed, furthermore the Scientific Identification Theory to Conduct Operation Research in Education Management (SITOREM) was applied to determine the priorities. The population includes all the elementary school teachers which are civil servants (PNS) in Bogor, Indonesia while 105 were selected as samples. The findings showed there is a positive correlation between situational leadership and teacher work productivity with a correlation coefficient of 0.783, and between self-efficacy and teacher work productivity with 0.782. This, therefore, means these two factors are influential in increasing the productivity of teachers. The novelty of this research was the use of SITOREM to highlight 7 indicators prioritized to be improved including leader behavior, delegation, direction, teacher achievement, facility use, efficiency, and managerial ability.